The conditions of alternations in derivatives paradigmas in Ukrainian, Russian and Polish languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article outlines the perspective of the research of verbal derivatives in Ukrainian in the context of theoretical achievements of modern linguistics, the conditions of alternations in derivatives paradigmas in Ukrainian, Russian and Polish languages.
Keywords: word-building morphonology; deverbatives; morphonema; morphonological processes; vowel and consonant alternations